Software Innovations to Support the Use of Social Media by Emergency Managers. Issue 4 (3rd April 2018) - Plotnick, Linda; Hiltz, Starr Roxanne
ABSTRACT: Although social media (SM) can be very useful for emergency managers (EMs), especially for providing situational awareness in the early stages of a disaster, many do not use it. This study is based on 477 responses to an online survey of U.S. county-level EMs. The two most important barriers to the use of SM for collecting information are lack of staff and fears of information overload. A number of potential software enhancements that could help overcome the limitations of SM for EMs were all rated as highly useful. Factor analyses were successfully performed on the sets of questions about barriers and about software enhancements. The barrier of trustworthiness of SM data was a significant predictor of usefulness of some of the enhancement factors. Differences related to characteristics of the respondents and their agencies are explored, and open-ended comments that help to explain the findings are summarized.